Eco-enzyme Apple Bar Soap for Skin Hydration in Older Adults - Elizabeth Yun Yun Vinsur; Berliany Venny Sipollo (Babali Nursing Research)
Introduction: This study investigated the effect of bar soap made from eco-enzymes and apples on the skin moisture of older adults. Eco-enzymes, produced by fermenting organic materials, have a pH of 4-5. Apples contain skin-beneficial compounds: fiber, antioxidants, vitamins, minerals, and phytonutrients. This research aimed to determine the impact of using this soap on the moisture of older adults' skin.